Wide excision of Basal Cell Carcinoma on the upper extremity: A case report - Maylita Sari; Putri Halla Shavira; Bagus Haryo Kusumaputra; Irmadita Citrashanty; M Yulianto Listiawan (Qanun Medika - Jurnal Kedokteran FK UMSurabaya, 2023)
Basal cell carcinoma (BCC) is the most common skin cancer, usually occurring in the sun-exposed area, such as the head and neck, but also seen in less common areas like the upper or lower extremities. The initial treatment of BCC lesions is completing tumor removal. One of the standard therapy for BCC is wide surgical excision, as it is highly efficacious. A 76-year-old female patient complained of a wounded blackish lump on the left upper extremity for about 2 years. It started small, then grew bigger. Complained of itchiness, but no pain. The lump easily bled when accidentally touched. Dermatology examination identified a hyperpigmented nodule about 1.5 cm, with a clear border, irregular raised edges, slightly rough surface, and erosion. A dermoscopy examination showed short-fine telangiectasia, blue-grey ovoid nests, and ulceration. The patient was diagnosed with suspected BCC and underwent biopsy, also wide excision surgery. Histopathology showed pigmented BCC. One month later, surgery proved a good result. Selecting appropriate therapy in BCC should be given to reduce the recurrence rate. The common treatment for BCC is wide surgical excision, because of its association with a low recurrence rate and the ability to confirm residual tumor pathologically. In conclusion, wide excision surgery is one of the effective therapy options for BCC.